Evaluating economic and environmental value of liner vessel sharing along the maritime silk road - Qiu, Xuan (2020)
The Belt and Road initiative is a novel exploration of China towards strategic collaboration with Eurasia countries to an extent of a larger scale with higher and deeper level of cooperation. To meet the growing global demand of transportation, increasing numbers of liner shipping companies collaborate and form alliances to share vessel capacity and reduce capital costs. Effective liner shipping vessel sharing is essential for the Belt and Road initiative in terms of building efficient maritime transport networks. In promoting environmental development, shipping companies are required to attain higher environmental standards. However, limited literature relates vessel sharing to environmental performance. This paper studies the impacts of liner vessel sharing from the economic and environmental perspectives. Two container allocation models are developed for the two scenarios: with and without vessel sharing. The carbon emissions in transportation are calculated under both scenarios. Numerical studies are carried out using services along the China-Indochina Peninsula Economic (CIPE) Corridor. Liner shipping companies could benefit from vessel sharing in terms of significant profit improvement. Vessel sharing could also benefit the environment by reducing the CO2 emissions dramatically.